The New Ice-Age: Frozen and Thawing Perceptions of Imagination - Hatt, Blaine E. (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
The article examines the importance of imagination in adult–child relationships in 21st-century experiential learning, where ICE is an acronym for Imagination Creativity Education. It explores, through hermeneutic phenomenology, the impact of imagination in the life-experiences of three school-aged children through the wonder of toying through shining new light on the autism spectrum, and through the debilitating effect of unbridled imagination. Life-experience is recognized as a foundational principle of imagination, and imagination is recognized as the catalyst for creative inquiry. The article discusses the vocative voice in children that calls out in its vulnerability to educators to act with appropriate, intentional, and responsible pedagogical relationality. The article concludes by highlighting the impact that imagination potentially holds for the future of education.